2021
DOI: 10.3390/f12111460
|View full text |Cite
|
Sign up to set email alerts
|

A Nonlinear Mixed-Effects Height-Diameter Model with Interaction Effects of Stand Density and Site Index for Larix olgensis in Northeast China

Abstract: Tree height is a basic input variable in various forest models, such as growth and yield models, biomass models, and carbon budget models, which serve as very important tools for the informed decision-making in forestry. The height-diameter model is the most important component of the growth and yield models and forest simulators. We developed the nonlinear mixed-effects height-diameter model with the interaction effects of stand density and site index introduced using data from 765 Larix olgensis trees in Jin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 38 publications
0
10
0
2
Order By: Relevance
“…In addition, the developed set of models significantly simplifies methods of growing stock volume estimation during sample-based forest inventory, since there is no need to measure heights of all tally trees on sample plots. Accordingly, the value of the variable h in the stem volume models (Table 3) can be estimated using equations (2)(3)(4)(5)(6).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the developed set of models significantly simplifies methods of growing stock volume estimation during sample-based forest inventory, since there is no need to measure heights of all tally trees on sample plots. Accordingly, the value of the variable h in the stem volume models (Table 3) can be estimated using equations (2)(3)(4)(5)(6).…”
Section: Resultsmentioning
confidence: 99%
“…The obtained data were summarised for each tree species and the average values of relative heights were calculated for all diameter classes observed in the study material. Equations (2)(3)(4) were used as mathematical models to characterize the h-d relationships. In particular, for pine, spruce, oak, beech, and ash, the following equation was used:…”
Section: Modelling H-d Relationshipsmentioning
confidence: 99%
“…It can also be viewed as a composite quantitative variable, a product of the interaction between the growth potential of the trees, speeding up the self-thinning process when high, and stand stocking. A study by Zhang et al (2021) revealed that the inclusion of the interaction effects of stand density and site index could significantly improve the prediction accuracy of the height-diameter model for Larix olgensis Henry. In addition, the modified Gaffrey's model derived here specifies the estimated tree height value according to the social status of the tree as well.…”
Section: Discussionmentioning
confidence: 99%
“…The h-d relationship in even-and uneven-aged forest stands is also important issue [9]. Some recent publications indicate that h-d relationships of trees depend on the origin of forest stands [10] and are closely related to their density [11]. Site conditions directly impact the h-d relationships of trees [12].…”
Section: Bilous Et Almentioning
confidence: 99%
“…are usually considered as factors that introduce random variations in the h-d relationships in forest stands of the same age. While fixed-effect models characterise the most typical relationship for a wide group of forest stands, mixed-effect models explain the random component of covariance of these characteristics for a particular forest stand [11]. Such models, apart from fixed-effect terms of the equation (the typical stand), also contain random-effect terms that describes remove the differences between each individual forest stand in relation to the typical one, thus revealing specific patterns of heights and diameters depending on random factors.…”
Section: Bilous Et Almentioning
confidence: 99%